THE DEVELOPMENT OF DIGITAL FINANCIAL SERVICES IN NON-BANK FINANCIAL INSTITUTIONS (CASE STUDY OF COOPERATIVE OF PONDOK PESANTREN SUNAN DRAJAT LAMONGAN) - Bella Suci Nur; Achsania Hendratmi (Universitas Airlangga, 2020)
The growing digital circulation in the bank and non-bank financial institutions has triggered the emergence of new competitors and changes in new market segmentation. This requires the Pondok Pesantren Cooperative to innovate and think to survive in the digital era as it is today. This study aims to see how the strategy of developing digital financial services in the Pondok Pesantren cooperative using the case study BMT Sunan Drajat Lamongan. This research uses a qualitative approach with a case study method. This research uses snowball sampling. Data collection techniques using direct interviews, documentation and observation. After data collection, the results of the study were analyzed using domain analysis to get conclusions. The results showed that one of the BMT Sunan Drajat's strategy in developing digital financial services in the digital age is by creating a number of digital innovations. Even though the application has not been implemented perfectly, the application has a positive influence on society.Keyword: digital financial services, digital finance, Pondok pesantren cooperative, strategy, non-bank financial institutionsREFFERENCE Al-QuranBower, J.L, dan Christensen, C.M. (1995). Disruptive technologies catching the wave. Harvard Business Review. 73(1), 43-53.Christensen, C.M. (1997). The Innovator’s dilemma: The revolutionary book that will change the way you do bussiness. New York: Boston Harvard business school Press.Christensen, C.M, dan Raynor, M.E. (2006). Solusi sang innovator. Jakarta: Serambi.Kasali, Rhenald. (2017). Disruption. Jakarta: Gramedia.Kasali. (2017). Meluruskan pemahaman soal disruption. Retrieved from www.kompas.comhttps://id.techninasia.com/jumlah-pengguna-smartphone-di-indonesia-2018Bank Indonesia. (2017). Survei Perbankan Triwulan IV-2016: Pertumbuhan kredit tahun 2017 diperkirakan meningkat. Diakses pada tanggal 16 Mei 2017 dari http://www.bi.go.idIriansyah, Fadli Yanuar. (2016). Investree mempertemukan peminjam dengan pemberi pinjaman secara online. Diakses pada tanggal 16 Mei 2017 dari http://www.techinasia.com/. Pratama, aditya hadi. (2017). Kumpulan startup fintech di Indonesia. Diakses pada tanggal 16 Mei 2017 dari http://www.techinasia.com/. Investree. (2016). Investree. Diakses pada tanggal 16 Mei 2017 dari http://Investree.id/. Majalah Peluang. (2017). Urgensi digitalisasi untuk koperasi. Fokus. Diakses pada tanggal 16 Mei 2017 dari http://www.majalahpeluang.com/. Bungin, Burhan. (2007). Penelitian kualitatif. komunikasi, ekonomi, kebijakan publik dan sosial lainnya. Jakarta: Putra Grafika.Hamidi Yusuf. (2008). Metode penelitian kualitatif. Malang: Universitas Muhammadiyah Malang Press.Moleong, Lexy J. (2009). Metode penelitian kualitatif. Bandung: PT. remaja Rosdakarya.Noor, Juliansyah. (2011). Metodologi penelitian: Skripsi, tesis, disertasi, dan karya ilmiah. Jakarta: Kencana.Yin, Robert K. (2015). Studi kasus design & metode. Jakarta: Raja Grafindo Persada.Nadzir, Moh. (2003). Metode penelitian. Jakarta: Ghalia Indonesia.Sugiyono. (2012). Metode penelitian kuantitatif, kualitatif dan R&D. Bandung: Alfabeta.Nurdiani, Nina. (2014). Teknik sampling snowball dalam penelitian lapangan. Comtech, 5(2), 1110-1118.Varian Danastya. (2018). Strategi lembaga amil zakat dalam menghadapi era disruptive innovation (studi kasus lembaga amil zakat al-azhar dan lembaga amil zakat inisiatif zakat Indonesia). Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Marginingsih Ratnawaty. (2019). Analisis SWOT technology financial (Fintech) terhadap industri perbankan. Cakrawala, 19(1), 55-60.Pramuka Agus Bambang, Siti Maghfiroh dan Sugiarto. (2017). Literasi keuangan pengelola koperasi pondok pesantren di kabupaten Banyumas. Materi Presentasi pada tanggal 17-18 November.Dipojono K. Hermawan. (2004). Perkembangan IPTEK dan Perspektif Al-Quran. Mimbar, 20(1), 1-6.